House of Mystery. [6], Safe as houses - Sturges, Lilah (DC Comics/Vertigo, 2011)
"In this volume featuring issues #26-30 of the acclaimed series, witches and goblins abound as Fig and The Witch Queen run from the Thinking Man's robot army that is fighting for control of the Summerlands"--Publisher's web site.